2015
DOI: 10.1007/s00068-015-0552-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sepsis in Korean trauma patients

Abstract: Among the risk factors identified in the literature, our research confirmed only the patients' age and ISS as risk factors for sepsis after trauma, and, additionally, identified emergency surgery as a risk factor in Korean patients. Therefore, trauma patients who have any of the risk factors mentioned above have a high risk of post-traumatic sepsis, which requires certain precautionary clinical measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…While there is experimental evidence of at least one benefit to the use of irrigation in trauma victims [39], our results strongly suggest an upper limit of 5L for the effluent. This has relevance for today's practice, since epidemiological evidence exist for the current use of Intraoperative Peritoneal Lavage for this indication in surgical practice [41][42][43][44][45][46][47][48][49][50]. Our trial has several limitations: Since damage control techniques were utilized when indicated (as per the contemporary accepted standard of care) it is very possible that the potential benefits and/or harms (or lack thereof) that the intervention has in this population remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in clinical management of trauma patients, major trauma results in approximately 15% of disabilities and 10% of deaths (Lord et al, 2014). Sepsis is one of the most serious complications post major trauma, which might result in progressive dysfunction of vital organs (Park et al, 2016). Sepsis and multiple-organ dysfunction syndromes (MODS) compound the systemic inflammation triggered by the original injury and are difficult to distinguish (Lindner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the context of certain infections, IL-33 was either protective or even deleterious because it can either play a beneficial role in the resolution of inflammatory processes, or it can contribute to aggravating inflammation, respectively [115, 125, 135]. Sepsis is a systemic inflammatory condition due to bacterial infection with limited therapeutic but also diagnostic options, which frequently occurs after trauma, and hides a high risk for mortality [4, 136138]. Interleukin-33 reduces mortality in septic mice after cecal ligation and puncture (CLP) due to increased neutrophil influx into the peritoneal cavity and enhanced bacterial clearance as compared with untreated mice [139].…”
Section: Danger Signals In Traumamentioning
confidence: 99%